1998
DOI: 10.1046/j.1365-3059.1998.00222.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of peanut stunt cucumovirus from naturally infected alfalfa in Iran

Abstract: A mechanically transmissible virus was isolated from a naturally infected alfalfa plant (Medicago sativa) in Karaj, Iran. It induced fern-leaf symptoms in Lycopersicon esculentum, general chlorosis and stunting in Arachis hypogoea, local lesions and systemic infection in Chenopodium quinoa, Phaseolus vulgaris and Vigna unguiculata but only local lesions in C. amaranticolor. In gel-immunodiffusion tests, it reacted strongly with an antiserum to peanut stunt cucumovirus (PSV), moderately with two of six antisera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Unincorporated nucleotides were removed with Probe Quant TM G-50 microcolumns (Pharmacia, Piscataway, NJ, U.S.A.). RNA denaturation and slot-blot hybridization were performed as described (Bananej et al 1998), except that the Gene Screen Plus transfer membrane (New Life Science Products, Boston, MA, U.S.A) was used and prehybridization and hybridization were performed at 42°C. Hybridization signals were scanned and imaged with a Molecular Dynamics Storm 840 PhosphoImager (Sunnyvale, CA, U.S.A.).…”
Section: Probes and Slot-blot Hybridizationmentioning
confidence: 99%
“…Unincorporated nucleotides were removed with Probe Quant TM G-50 microcolumns (Pharmacia, Piscataway, NJ, U.S.A.). RNA denaturation and slot-blot hybridization were performed as described (Bananej et al 1998), except that the Gene Screen Plus transfer membrane (New Life Science Products, Boston, MA, U.S.A) was used and prehybridization and hybridization were performed at 42°C. Hybridization signals were scanned and imaged with a Molecular Dynamics Storm 840 PhosphoImager (Sunnyvale, CA, U.S.A.).…”
Section: Probes and Slot-blot Hybridizationmentioning
confidence: 99%
“…Despite their importance, limited information is available on the occurrence of viruses of the family Bromoviridae in forage legume fields in Iran, although the occurrence of Alfalfa mosaic virus and two cucumoviruses including Cucumber mosaic virus and PSV has been previously reported (Bananej et al. ; Massumi et al. ).…”
Section: Introductionmentioning
confidence: 99%
“…Nos. KM823526-KM823529) were clustered in a new subgroup, which we tentatively named subgroup V. Bananej et al [3] previously reported an Iranian PSV isolate (PSV-I). Sequence analysis of parts of RNA1 and 2 by Hajimorad et al [12] showed that PSV-I is more closer to the W strain than to the E strain; nevertheless PSV-I could not be placed into subgroup II and consequently was named 'atypical old world' strain of the virus.…”
Section: Discussionmentioning
confidence: 88%
“…Currently alfalfa is widely grown in different parts of Iran with the exception of three western provinces [30]. PSV was reported for the first time in Iran on the basis of biological, serological and physico-biochemical properties by Bananej et al [3]. Following further characterization of this isolate based on Northern blot hybridization by Hajimorad et al [12], it was placed in subgroup II.…”
Section: Introductionmentioning
confidence: 99%